Mak Nyah cabaret dance performance at three nightclubs in Klang Valley / Sarah Low May Poh - Sarah Low , May Poh (2018)
Transgendered women in Malaysia are known as Mak Nyah. The term refers to “woman in transition”. Mak Nyah performances such as stand up comedy and dance performances at weddings, nightclubs, corporate events existed even before the 1980s but these performances were not strictly policed by the Malaysian state. With the 1980s political motive to uphold the Asian Values, increased Islamization and establishment of the 1983 Fatwa Law in Malaysia, the state, media, and nation’s perception towards transgendered people, particularly the Mak Nyah community, have been affected at large. These groups were often oppressed, stigmatised and ostracised. In this thesis, I discuss the economies of visibility in relation to spectatorship and agency. Political agenda and religious constraints have made it difficult for Mak Nyah artists to publicly and openly express themselves via speech, performance, and attire. In this process, they have slowly lost their voice, access, and visibility in public spaces. However, Mak Nyahs are able to express their desired gender through agencies such as cabaret dancing. Mak Nyah cabarets are variety shows that comprise of dance, music, parade, and stand-up comedy and appeals to spectators. Three nightclubs that I investigate in Klang Valley hire these Mak Nyah dancers as they are often seen involving and engaging their spectators during performances and giving audiences a positive experience. Through the intersection of dance, history, and ethnology, this thesis examines how dance has allowed Mak Nyah cabaret dancers, in chosen nightclubs, Club A, B and C, the platform for visibility through agency and spectatorship. This thesis also traces the survival, mobility, and flexibility of Mak Nyah cabaret dancers by focusing on performances in the nightclubs and real-life narratives outside the nightclubs.